Relaying Selection Based Multiple Access Relay Channel - Karabulut, Muhammet Ali; Ozdemir, Ozgur; Ilhan, Haci (IEEE, 2016)
Relay selection in case of fast cascade Rayleigh fading channels has been examined in multiple access relay channel structure which is one of the high spectral efficiency network coding applications. Error performance analysis of MARC system has been made for noncoherent binary frequency shift keying (BFSK) and it has been shown that the proposed approach provides full diversity gain.
Keywords: relay selection; multiple access relay channel; noncoherent BFSK; SYSTEMS; Engineering